Produksi senyawa metabolit sekunder dari tumbuhan obat - Aliefman Hakim; A. Wahab Jufri (Pendidikan Matematika, FKIP Universitas Mataram, 2021)
Secondary metabolites were needed by researchers as raw materials for drugs, raw materials for the synthesis of target molecules, bioactive compounds, and model compounds. But until now, there were no producers that supply secondary metabolite compounds in Indonesia, so it is very difficult to find them in the domestic market. The need for secondary metabolite compounds has been purchased from abroad at very high prices. On the other hand, Indonesia has a lot of plant diversity which is the source of secondary metabolite compounds. Modification of several procedures for isolation of secondary metabolites has been carried out in the framework of the production of secondary metabolites.